Music visualization - Chng, Cassandra Chi Ern (2018)
The differences in place of origin and instruments between Western and Chinese music are merely skin-deep. Differences in tuning and therefore scales posits a far deeper contrary in the harmony each music holds. Perceptually, due to the distinction of instruments and tuning, Western and Chinese music can be easily told apart. Yet to what extent is the music unique or similar to one another? This research will explore the contrast in harmony in the form of chords and voice leading in chord progressions from both kinds of music. The disparity will be shown visually through the movement of voices from one chord to another. This report will detail the background research of Western and Chinese music from an acoustic point-of-view. The research will serve as the basis to establish differences between them by numbers. The comparison of both music by chords and chord progressions will be visually displayed through a simple Python code.